The views of international students regarding university support services in Australia: A case study - Roberts, P.; Boldy, Duncan; Dunworth, K. (Shannon Research Press, 2015)
This paper reports on a study aimed at developing an improved understanding of the support needs of international students. Using a case study approach at one Australian university, a three stage data collection process was adopted: interviews with key support service providers in the university, student focus groups, and a large-scale survey. Emphasis was placed on identifying the issues that are significant to international students in terms of their study experience, the services they consider as valuable and the factors that contribute to take-up. The findings reveal that, while most respondents felt that the range of support services provided is appropriate, current services could be improved by offering a more student-centred service structure and delivery. Issues identified as influencing service use include the institutional culture, perceived importance and awareness of services, the quality of information provided about those services, ease of access, timeliness of service provision and cost.